Analisa Superdecisions Untuk Menentukan Pilihan Produk Memori Komputer - Arsanto Narendro; Tatang Wirawan Wisnuadji (CV. Multi Kreasi Media, 2025)
The decision-making process often becomes a complex challenge when it involves various interrelated criteria; thus, carelessness at this stage has the potential to trigger fatal errors. To minimize such risks, a supporting instrument in the form of specialized software is required to process intricate decision parameters. One available technological solution is SuperDecisions, a software that adopts the principles of the Analytic Hierarchy Process (AHP) method to perform analysis, synthesis, and policy determination in multifaceted situations. In this study, data gathered through questionnaires were converted into variables compatible with the SuperDecisions system. The final results processed by this software provide a ranking of all available alternatives to determine the best option. Based on the system output in this case, DDR3 memory was selected as the winning alternative because it was deemed the most optimal in meeting the entirety of the established criteria.